Brachypterous and micropterous species of the genus Hormius Nees (Hymenoptera: Braconidae: Hormiinae) - Belokobylskij, Sergey A (Zootaxa, 2026)
The known brachypterous and micropterous species of the cosmopolitan genus Hormius Nees, 1819 are reviewed. Two new species of this genus, H. haeselbarthi sp. nov. and H. helleni sp. nov., are described and illustrated. The distribution of H. minialatus Tobias, 1977 is discussed. A key for determination of the Hormius subgenera and all known brachypterous and micropterous species is provided.